Human Rights and Anti-Semitism after Gaza - Grosfoguel, Ramón; University of California, Berkeley, USA (Editorial Pontificia Universidad Javeriana, 2009)
This article analyzes the consequences of the latest Israel massacres in Gaza in relation to their global consequences in reference to human rights and global Anti-Semitism in actuality. The first part examines the consequences of Gaza in light of human rights. The second part is an analysis of the consequences of Gaza in reference to global AntiSemitism. The last part analyzes global fundamentalism in the current world.